2022
DOI: 10.1002/hed.26991
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with patient‐reported fatigue among long‐term oropharyngeal carcinoma survivors

Abstract: Background The study objective is to identify risk factors associated with fatigue among long‐term OPC survivors. Methods This cross‐sectional study included disease‐free OPC survivors treated curatively between 2000 and 2013 who were surveyed from September 2015 to July 2016. The outcome variable was patient‐reported fatigue. Multivariable logistic regression was used to identify factors associated with moderate to severe fatigue. Results Among 863 OPC survivors, 17.4% reported moderate to severe fatigue. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Until now, data on CF in HNC survivors have been limited, but this study showed that as many as one-third of the survivors suffered from this condition. While a previous report of a more selected HNC population described lower levels [59], the proportion of HNC survivors affected by CF in this study was at the same high level as for survivors treated for breast cancer and lymphoma [23,26,36]. This added information suggests that a considerable number of HNC survivors may require assistance and guidance in handling CF, and efforts should be made to accommodate these needs.…”
Section: Discussionmentioning
confidence: 47%
“…Until now, data on CF in HNC survivors have been limited, but this study showed that as many as one-third of the survivors suffered from this condition. While a previous report of a more selected HNC population described lower levels [59], the proportion of HNC survivors affected by CF in this study was at the same high level as for survivors treated for breast cancer and lymphoma [23,26,36]. This added information suggests that a considerable number of HNC survivors may require assistance and guidance in handling CF, and efforts should be made to accommodate these needs.…”
Section: Discussionmentioning
confidence: 47%
“…Interestingly, we found that post‐dialysis fatigue was significantly more frequent in female patients; it is the first time that such result is reported, and it seems that further studies are required to clarify the underlying mechanisms. However, there is evidence that the frequency of fatigue is higher in female patients also in other chronic diseases such as cancer 40–43 and multiple sclerosis 44,45 …”
Section: Discussionmentioning
confidence: 99%